LIGHT IN THE WORKS OF GIACOMO BALLA IN THE PERSPECTIVE OF LIGHT ART GENESIS - Anna M. Spiridonova (Russian Studies in Culture and Society)
The article is devoted tо the specific question in Russian art history – to the problem of light in the works of J. Balla from the perspective of Light art genesis. The insufficiently researched genesis of light art .in Modernism and Italian Futurism is followed by the incomplete understanding of phenomenon. This circumstance requires an appeal to the historical roots of Light art, particularly, to the period when artists started including artificial light into the practice of fine art and started using it as a medium.